The learning with care training materials - Judy Furnivall; Barbara Hudson (Scottish Journal of Residential Child Care)
Outlines the content of the Learning with Care training materials, commissioned by the Scottish Executive through the Learning with Care project. The materials were sent to every local authority and residential child care provider in Scotland, with many of the authorities already developing plans to deliver the training.